Truncated gRNA reduces CRISPR/Cas9-mediated off-target rate for MSTN gene knockout in bovines - Zheng-wei ZHOU; Guo-hua CAO; Zhe LI; Xue-jie HAN; Chen LI; Zhen-yu LU; Yu-hang ZHAO; Xue-ling LI (Journal of Integrative Agriculture)
The CRISPR/Cas9 mediates efficient gene editing but has off-target effects inconducive to animal breeding. In this study, the efficacy of CRISPR/Cas9 vectors containing different lengths of gRNA in reduction of the off-target phenomenon in the bovine MSTN gene knockout fibroblast cell lines was assessed, providing insight into improved methods for livestock breeding. A 20-bp gRNA was designed for the second exon of the bovine MSTN gene, and CRISPR/Cas9-B was constructed to guide the Cas9 protein to the AGAACCAGGAGAAGATGGACTGG site. The alternative CRISPR/Cas9-19, CRISPR/Cas9-18, CRISPR/Cas9-17 and CRISPR/Cas9-15 vectors were constructed using gRNAs truncated by 1, 2, 3 and 5 bp, respectively. These vectors were then introduced into bovine fetal fibroblasts by the electroporation method, and single cells were obtained by flow cytometry sorting. PCR was performed for each off-target site. All samples were sequenced and analyzed, and finally the efficiency of each vector in target and off-target sites was compared. The CRISPR/Cas9-B vector successfully knocked out the MSTN gene, but the off-target phenomenon was observed. The efficiencies of CRISPR/Cas-B, CRISPR/Cas9-19, CRISPR/Cas9-18, CRISPR/Cas9-17 and CRISPR/Cas9-15 in triggering gene mutations at MSTN targeting sites were 62.16, 17.39, 7.69, 74.29 and 3.85%, respectively; rates of each at the Off-MSTN-1 locus were 52.86, 0, 0, 8.82 and 0%, respectively; all were 0% at the Off-MSTN-2 locus; rates at the Off-MSTN-3 site were 44.87, 51.72, 86.36, 0 and 50%, respectively. The efficiency of the CRISPR/Cas9-17 plasmid in the MSTN site was higher than that in the CRISPR/Cas9-B plasmid, and the effect at the three off-target sites was significantly lower. This study demonstrated that the CRISPR/Cas9-17 plasmid constructed by truncating 3 bp gRNA can effectively reduce the off-target effect without reducing the efficiency of bovine MSTN gene targeting. This finding will provide more effective gene editing strategy for use of CRISPR/Cas9 technology.